Negative refraction in all-dielectric metamaterials - Yap, Jia Wei (Nanyang Technological University, 2021)
The speed of light in a medium is related to their electric permittivity and magnetic permeability. In nature, the permittivity and permeability of most dielectric and conventional materials are positive. In this project, negative permittivity and negative permeability will be investigated, which is otherwise known as double negative material. DNG materials do not exist in nature, but in 1999, they were made possible by the development of metamaterials (artificially structured materials). However, most of the metamaterials used are metallic (e.g., split ring resonators), which results in high dissipation loss. Hence, the objective of this project is to explore a new approach to achieve low loss negative refraction by making use of all-dielectric resonators. Wolfram Mathematica will first be used to calculate the effective electric permittivity and effective magnetic permeability, before plotting a graph and retrieving their data values. COMSOL Multiphysics will then be used to model an array of dielectric resonators using these values. Finally, electromagnetic wave will be used to propagate through the resonators to observe negative refraction.